Pertukaran Sosial Sistem bagi Hasil Nelayan Bagang Kambang di Kampung Bugis Kecamatan Muncar Kab. Banyuwangi - OVIE FAIZ PRATAMA (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
ABSTRACT The profit-sharing system is a form of cooperation commonly applied in capture fisheries, including among lift-net (bagang kambang) fishermen in Kampung Bugis, Kedungrejo Village, Muncar District, Banyuwangi Regency. This system regulates the distribution of fishing proceeds between the owner of the lift-net and the workers based on a mutually agreed arrangement. This study aims to examine the profitsharing system implemented in the bagang kambang fishery business and to analyze the relationship between owners and workers through the perspective of Peter M. Blau’s Social Exchange Theory. This study employed a qualitative research method with a descriptive approach. Data were collected through observation, interviews, and documentation. The research informants consisted of bagang kambang owners and workers involved in fishing activities. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. Data validity was ensured through source triangulation by comparing information obtained from different informants. The results of the study indicate that the profit-sharing system in the bagang kambang fishery business is implemented with a distribution of 60% for the owner and 40% for the workers. This distribution is based on the contribution of each party, where the owner provides capital, production facilities, and bears business risks, while the workers contribute labor, time, experience, and skills in fishing activities. From the perspective of Peter M. Blau’s Social Exchange Theory, the relationship between owners and workers reflects the elements of reward and cost, power, and dependency. The reward received by the owner is in the form of business profits, while workers obtain income from the fishing catch. The costs borne by the owner include the initial investment for constructing a bagang kambang, which exceeds IDR 40,000,000, operational expenses, and business risks. Meanwhile, workers bear costs in the form of labor, time, occupational risks at sea, and income uncertainty that depends on the fishing catch. The owner’s power arises from control over capital and production facilities, although it is exercised through cooperation and mutual deliberation. Furthermore, a reciprocal dependency relationship exists because owners require labor to operate the business, while workers depend on owners as providers of employment and sources of income.
Keywords: Profit-Sharing System; Bagang Kambang Fishermen; Social Exchange Theory; Peter M. Blau; Muncar.